Matching of XEN®45 and PRESERFLO™ MicroShunt cases: Outcomes of a 3-year follow-up - Cemre Altas; Marcus Walckling; Tobias Brockmann; Fabian Stelzle; Anselm Jünemann; Thomas Fuchsluger (PLoS ONE, 2025)
Objective To compare long-term outcomes of XEN®45 (XEN) and PRESERFLO™ MicroShunt (PRESERFLO) implants in the surgical management of glaucoma over a 3-year follow-up period, focusing on intraocular pressure (IOP) reduction, need of medication, surgical success, and postoperative complications. Methods A retrospective, matched case control study was conducted, including 42 eyes with preceded implantation of a XEN or PRESERFLO. Patients were statistically matched using SPSS algorithms for glaucoma diagnosis, previous surgery, and demographics. Standardized success criteria defined surgical outcomes: complete success (IOP ≤ 15 mmHg or ≤ 18 mmHg without medications) and qualified success (IOP ≤ 15 mmHg with < 3 medications). Postoperative care and needling or revision interventions were recorded. Statistical analyzes included Wilcoxon, Mann-Whitney U, and t-tests. Results Both devices significantly reduced IOP and glaucoma medication over 3 years. XEN reduced IOP from 22.1 ± 8.6 mmHg to 13.5 ± 3.8 mmHg, while PRESERFLO reduced IOP from 22.1 ± 6.6 mmHg to 12.6 ± 4.0 mmHg (p > 0.05 for between-groups, 3 years postoperative). Medication use decreased from 2.4 ± 1.0 to 0.9 ± 1.4 for XEN and 3.1 ± 1.1 to 1.1 ± 0.9 for PRESERFLO (p > 0.05 for between-groups). Surgical success rates were similar after 3 years. PRESERFLO showed fewer postoperative revisions (28.6% vs. 42.9% for XEN; p > 0.05). Early hypotony occurred more frequently with XEN (17 vs. 7 cases; p = 0.029). Conclusion Both XEN and PRESERFLO effectively reduce IOP and the need for glaucoma medication, with comparable surgical success rates after 3 years. PRESERFLO demonstrated a lower revision rate and reduced frequency of early postoperative hypotony. These findings support both implants as viable options for minimally invasive glaucoma surgery, with low risk profiles.